Behavioral response of Bornean ungulates, including bearded pigs and sambar deer, to anthropogenic disturbance in Sabah, Malaysia - Miyabi Nakabayashi; Tomoko Kanamori; Aoi Matsukawa; Joseph Tangah; Augustine Tuuga; Titol Peter Malim; Henry Bernard; Abdul Hamid Ahmad; Ikki Matsuda; Goro Hanya (Elsevier B.V., 2025)
Understanding wildlife behavioral responses to anthropogenic disturbance is crucial for assessing its effects and managing protected areas. We used camera traps to investigate the behavioral responses of two of the most frequently hunted Bornean ungulate species, bearded pigs (Sus barbatus) and sambar deer (Rusa unicolor), to anthropogenic disturbance in three protected areas in Sabah, Malaysia, that have varying levels of human activity. We found that human activities generally influence the activity patterns of both ungulates, albeit with variations among the sites. Temporal activity levels of both species would be affected by anthropogenic disturbance; temporal activity levels of bearded pigs were generally low where poaching of this species is reported and both species reduced their activity during daytime, the period of highest probability of encountering humans. Bearded pigs approached plantations during times of low human activity, presumably to forage, indicating that they adjust their spatiotemporal activity patterns to minimize human contact. Conversely sambar deer approached plantations when humans were active during the daytime, suggesting acclimation to non-lethal human contact to maximize energy intake. We observed a reduction in active times for both species at sites of high anthropogenic disturbance. Despite these challenges, both species demonstrated behavioral adaptability to anthropogenic disturbance by utilizing artificial environments such as roads and oil palm plantations probably as foraging places, thereby potentially compensating for reduced active times especially for feedings. Our study underscores the negative impact of human activities on the activity patterns of these two ungulate species. Meanwhile, they showed behavioral plasticity to anthropogenic disturbance by utilizing food resources in artificial environments efficiently. Our findings highlight the need for additional research into the behavioral responses of ungulates in Southeast Asia.